Pengaruh Inflasi terhadap Peningkatan Penyaluran Pembiayaan melalui Perbankan Syariah di Indonesia - Biyati Ahwarumi; Luluk Syafa'ati (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2023)
The research method used in this study is quantitative research by calculating the SPSS program through a simple regression analysis technique, and the data used is secondary data in the form of annual time series data starting in 2020-2021 from the official website of the Financial Services Authority (OJK), Central Board Statistics (BPS) and Bank Indonesia (BI) according to research variables. The results of the statistical test can be concluded that partially the inflation-free variable (ϰ) in the 2020-2021 research year has a significant effect on the dependent variable increasing the distribution of financing through Islamic banking (Y) in the 2020-2021 research year. Inflation has a negative effect on the grounds that if inflation rises, financing will decrease because people's purchasing power decreases and if financing is increased it will be able to reduce inflation